ANALISIS ACTIO PAULIANA DALAM KEPAILITAN TERKAIT PEMBERIAN FASILITAS KREDIT TERHADAP PERUSAHAAN DENGAN JAMINAN ATAS NAMA DIREKSI - Salvian salmon; Christine S.T. Kansil (Jurnal Hukum Adigama, 2018)
The Actio Pauliana legal institution was formed in Article 41 and Article 42 of Law Number 37 of 2004 concerning Bankruptcy and Delay of Obligations to Pay Debt with the aim of avoiding legal actions that could harm creditors in their legal relationship with bankrupt debtors. The case of actio pauliana also occurred in the bankruptcy of PT Sumber Urip Sejati Utama, so this study uses normative descriptive analytical research methods with case studies. Actio pauliana's law enforcement is very difficult to do, in the case of the author, Actio Pauliana is actually in accordance with the relevant law, but requires strong evidence because the judge prioritizes formal proof. Regarding differences in decisions, this occurs because of the consideration of a judge who is lacking in the first level court so that it is canceled at the appellate level, whereas this occurs because the curator's evidence is still lacking. The author concludes that at this time, proof of actio pauliana in the case that the author adopted was in accordance with the relevant law but the verification by the curator must be done formally. While the differences in decisions at the first level court and cassation occur because the judge prioritizes legal certainty.